Reinventing Wiḥdat al-Wujūd: Locality, Cultural Catharsis, and Spirituality of Majelis Shalawat Muhammad in East Java - Rubaidi Rubaidi; Husna Jamaludin; Dwi Setianingsih (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2022)
This paper examines the teaching of Wiḥdat al-Wujūd in Majelis Shalawat Muhammad in Surabaya and Bojonegoro from 2011 to the study period. As a Sufi “organization,” Majelis Shalawat under Gus Kahar and Gus Mursyidin (murshid) learned the Sufi thoughts on Ibnu ‘Arabi doctrine. This article was established on qualitative research using participatory techniques, in which the author was deeply involved in the Majelis Sahalawat. On the one side, this paper explores the Sufi education system of Gus Kahar and Gus Mursyidin from ‘lelaku’ or riyāḍah. The result of the inquiry presented a connection between the sanad and Sufi scholars in Java. On the other hand, Sufi thought in various Majelis Shalawat indicates a strong Wiḥdat al-Wujūd thought. This article argues that the thought of Wiḥdat al-Wujūd continuing living from time to time is proven by the thoughts of the two murshids in Majelis Shalawat Muhammad in East Java. These two murshids do not directly use the term Wiḥdat al-Wujūd; instead, the term aḥad or aḥadiyah is more frequent, which is synonymous with Wiḥdat al-Wujūd doctrines of Ibnu ‘Arabi. It also emphasizes that Indonesian Sufism denotes the importance of locality and cultural catharsis within Javanese Muslim’s spiritual practices.